Mulberry, Clay County - Lynk, Johnathan (Kansas State University, The Chapman Center for Rural Studies, 2011)
Mulberry was once a Clay County township with thriving stores, hotels, and other businesses, a place where settlers could come with new ideas and prosper. At the same time Mulberry settlers were chasing the new "American Dream" they themselves were being caught by the tremendous destruction caused by natural disasters.
Johnathan Lynk, “Mulberry, Clay County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/27.
Keywords: C.C. Funnel; Clay County; J.G. Haynes; Mulberry; Clay County; Republican River Valley